Apreciación general de la situación de la Educación Matemática en Latinoamérica con base en los informes nacionales - Comité Interamericano de Educación Matemática, CIAEM (2010)
It is done a general balance on the Mathematics Education in the Latin- American countries. Particularly, some aspects are analyzed: mathematics curriculum for primary and middle levels; pre- and in-service education of mathematics teachers; texts and didactic publications; Mathematics Education at the university; the role of mathematical associations and out-of-school activities concerning the mathematics.